92.8k views
3 votes
Solve the equation for a: z = ma – b

Solve the equation for a: z = ma – b-example-1

1 Answer

2 votes

From the given question

There are given that the equation:


z=ma-b

Now,

For finding the value of a, first, add b in both sides of the equation

So,


\begin{gathered} z=ma-b \\ z+b=ma-b+b \\ z+b=ma \end{gathered}

Then,

Divide by m on both sides the above equation


\begin{gathered} z+b=ma \\ (z+b)/(m)=(ma)/(m) \\ a=z+b \end{gathered}

Hence, the value of a is z + b.

User Shlomie
by
6.5k points